2020
DOI: 10.2217/fnl-2019-0029
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Propranolol with and without Rosuvastatin on Migraine Attacks: A Triple Blind Randomized Clinical Trial

Abstract: Aim: To investigate the effect of rosuvastatin in combination with propranolol in reducing migraine attacks. Patients & methods: In a clinical trial study with census method, 120 patients with migraine headache were included. Patients were randomly assigned (using block randomization) to either propranolol (10 mg twice a day) with rosuvastatin (10 mg daily; intervention group [n = 60]) or propranolol (10 mg twice a day) with placebo (control [n = 60]). Results: The numbers of attacks were significantly dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Additionally, Sahebnasagh et al found that combining sodium valproate with atorvastatin resulted in a reduction in the number of attacks and pain severity [ 29 ]. Mazdeh et al reported a significant reduction in the number of attacks when using propranolol and rosuvastatin [ 30 ]. In addition to the potential in alleviating the attack frequency and severity of migraines, the use of statins in migraine prevention may have the added advantage of addressing endothelial dysfunction, a condition associated with CHD and ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Sahebnasagh et al found that combining sodium valproate with atorvastatin resulted in a reduction in the number of attacks and pain severity [ 29 ]. Mazdeh et al reported a significant reduction in the number of attacks when using propranolol and rosuvastatin [ 30 ]. In addition to the potential in alleviating the attack frequency and severity of migraines, the use of statins in migraine prevention may have the added advantage of addressing endothelial dysfunction, a condition associated with CHD and ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Aside from the increased cardiovascular risk, lipid parameters have been associated directly with the increased burden (frequency‐wise) of the disease 63,64 . Furthermore, cholesterol‐lowering medications (namely statins) have demonstrated favorable efficacy properties in the prevention of the disease 65–67 . It is possible that these effects are a subsequent of the improvement of endothelial dysfunction and the reduction of vascular wall inflammation mediated by statins 68 .…”
Section: Discussionmentioning
confidence: 99%
“…63,64 Furthermore, cholesterol-lowering medications (namely statins) have demonstrated favorable efficacy properties in the prevention of the disease. [65][66][67] It is possible that these effects are a subsequent of the improvement of endothelial dysfunction and the reduction of vascular wall inflammation mediated by statins. 68 Aside from the above-mentioned general properties, statins, they downregulate the production of CGRP and substance p, 69 as well as attenuate the NF-kB activation in the trigeminal nucleus caudalis, 70 which are believed to play an important role in the pathophysiology of migraine.…”
Section: Ta B L E 1 Methodological Features and Participant Demograph...mentioning
confidence: 99%
“…Observational studies have reported that disorders in the metabolism of lipids, including cholesterol and low-density lipoprotein cholesterol (LDL-C), may increase susceptibility to migraine 4 , 5 . Additionally, it has been speculated that certain lipid-lowering drugs such as statins possess migraine-ameliorating properties 6 8 . However, the available studies on the association between statins and migraine risk disagree, and the causal relationship remains uncertain 6 10 .…”
Section: Introductionmentioning
confidence: 99%